The Effect of Regional Gross Domestic Product (GDP) and Development Expenditure on Employment in the District Luwu - Patra, I Ketut; Wahyuny, Sri (Journal of Social and Development Sciences, 2016)
This study aims to assess the economic growth and the factors that influence the economic growth in the local government system by increasing the production of goods and services measured by Gross Domestic Product (GDP) and the policy of government expenditure (development) that can directly drive growth to finance economic development in the field of social economy and the public, both the development of physical and non-physical. This study uses multiple regression analysis by the least squares method (Method of Ordinary Least Square) OLS. These results indicate that the budget Revenue Expenditure Luwu, particularly in development spending has been a major contribution to regional development Luwu. With increasing economic growth and rising Luwu regency Regional Budget Builders Luwu district each year, then it will affect the employment opportunities for local people Luwu.